Terrorism and Organized Crime - Challenges to the Global Security (Kriminalističke teme, 2007)
Terrorism and organized crime represent very explicitly challenges to the global security, respectively they show as the major problems for the global security. Its contributed by many large geopolitical event and global social changes, as a result those events, which are happened at the end of XX and at the beginning of XXI century. Globalization, as the process of penetration and incorporation of the world, by positive, has some certain negative implications. Some of them bring some current problem, such as real terrorism, especially suicidal terrorism, some new types crime (including new types) of organized crime), appear of new security challenges, threats and risks, and appearance of many others social negative occurrences. Terrorism and organized crime characterize much more complexly appearances, especially hard anticipation and by it complicated prevention and fighting, and bigger mobility, which presents to the necessary of watching to these events for many aspects. Terrorism and organized crime (observing individual or in interaction) appear as the challenges to the global security, even they represent direct source, shapes or risk for security certain country, regions or even international community at all. Terrorism and organized crime represents threats to security of individual country, for other they are only possible challenges and risks, but for third, actually, they are the most clearly threats for this security.